Selective fluorogenic imaging of hepatocellular H2S by a galactosyl azidonaphthalimide probe - Shi, De-Tai; Zhou, Dan; Zang, Yi; Li, Jia; Chen, Guo-Rong; James, Tony D.; He, Xiao-Peng; Tian, He (Chemical communications (Cambridge, England), 2015)
We have developed a galactosyl azidonaphthalimide probe for the selective fluorogenic imaging of hepatocellular H2S, an important gaseous transmitter produced in the liver.We have developed a galactosyl azidonaphthalimide probe for the selective fluorogenic imaging of hepatocellular H2S, an important gaseous transmitter produced in the liver.